2016
DOI: 10.1513/annalsats.201606-426fr
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Systemic Sclerosis–related Interstitial Lung Disease: A Review of Existing and Emerging Therapies

Abstract: Although interstitial lung disease accounts for the majority of deaths of patients with systemic sclerosis, treatment options for this manifestation of the disease are limited. Few high-quality, randomized, controlled trials exist for systemic sclerosis-related interstitial lung disease, and historically, studies have favored the use of cyclophosphamide. However, the benefit of cyclophosphamide for this disease is tempered by its complex adverse event profile. More recent studies have demonstrated the effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
52
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 107 publications
1
52
0
3
Order By: Relevance
“…SSc is a chronic autoimmune CTD of unknown aetiology, associated with considerable morbidity and increased mortality [55]. Reported percentages of patients with SSc who develop ILD range 35-90%; SSc-ILD often manifests as NSIP and is a major cause of morbidity and mortality [56][57][58][59]. Although SSc can occur at any age, patients are usually 30-60 years of age, and women are more likely to develop SSc than men [55,60,61].…”
Section: Ssc-associated Ildmentioning
confidence: 99%
See 1 more Smart Citation
“…SSc is a chronic autoimmune CTD of unknown aetiology, associated with considerable morbidity and increased mortality [55]. Reported percentages of patients with SSc who develop ILD range 35-90%; SSc-ILD often manifests as NSIP and is a major cause of morbidity and mortality [56][57][58][59]. Although SSc can occur at any age, patients are usually 30-60 years of age, and women are more likely to develop SSc than men [55,60,61].…”
Section: Ssc-associated Ildmentioning
confidence: 99%
“…The cause of SSc is unknown, but its onset is associated with the interaction of environmental factors (including occupational, dietary, medical and lifestyle exposures and possibly infectious agents) in genetically predisposed individuals (e.g. African-American race) [55,58].…”
Section: Ssc-associated Ildmentioning
confidence: 99%
“…[3, 4] Given concerns regarding the potential long-term toxicity associated with CYC use, mycophenolate mofetil (MMF) has emerged as an alternative treatment agent for SSc-ILD. [5] Uncontrolled studies have demonstrated that MMF may prevent progression of SSc-ILD. [612]…”
mentioning
confidence: 99%
“…emerged as an alternative treatment for SSc-related ILD (5). Uncontrolled studies have demonstrated that MMF may prevent progression of SSc-related ILD (6)(7)(8)(9)(10)(11)(12).…”
mentioning
confidence: 99%
“…There is no established algorithm for the management of SSc-ILD, but patients with advanced ILD on HRCT, or ILD plus a decline in lung function or symptoms, generally undergo treatment with immunosuppression [29][30][31][32][33]. The treatment recommendations for SSc issued by the European League Against Rheumatism (EULAR) use a stringent selection of randomized controlled trials as supportive evidence.…”
Section: Current Treatment Of Ssc-ildmentioning
confidence: 99%